If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5 + 7 = 2x + -9 Reorder the terms: -5 + 7 + 3x = 2x + -9 Combine like terms: -5 + 7 = 2 2 + 3x = 2x + -9 Reorder the terms: 2 + 3x = -9 + 2x Solving 2 + 3x = -9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + 3x + -2x = -9 + 2x + -2x Combine like terms: 3x + -2x = 1x 2 + 1x = -9 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + 1x = -9 + 0 2 + 1x = -9 Add '-2' to each side of the equation. 2 + -2 + 1x = -9 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = -9 + -2 1x = -9 + -2 Combine like terms: -9 + -2 = -11 1x = -11 Divide each side by '1'. x = -11 Simplifying x = -11
| 15s^2-8s+1=0 | | 9x+5(35-x)=287 | | 6(3x+1)=3x-9X | | 1/4x+4=y | | y^3=-21 | | -12x+2(x-5)+9x=3x-10 | | x+y=15andx-2 | | -3.5=x/7 | | 8b-9y/4b-b-5y/4b | | b-9y/4b-b-5y/4b | | 8b-9y/4b-b-5y/4b=0 | | 2x^3-1-1=0 | | 20+3m+6m=92 | | -52^1/2 | | 11/2d=8 | | 1/5(10x-4)=7 | | -11/2d | | (4x+15)+(-5+2x)+(-10+6x)=360 | | 144/2 | | -[6z-(17z+9)]=9+(10z+1) | | 0=24x^3+20x^2-54x-45 | | 10+25=-5(9x-7) | | 2x-8y-9x+6y= | | 5x+5=49 | | (x-7)(x^2+10x+16)=0 | | 39x+52-14x-35=5x-13 | | (x-6)(x^2+9x+20)=0 | | 3x=16-1 | | 5x^2+25=-20 | | -16x^2+24x+50=0 | | 0.5(x-1/3) | | -2/-3d=8 |